Collective learning and COVID‐19 mitigation in Ghana. Issue 3 (11th January 2022) - Osei‐Kojo, Alex; Kenney, Paul Lawer; Damoah, Clement Mensah; Ahenkan, Albert
Abstract: COVID‐19 has created significant uncertainty and disruption among governments and people across the globe. Policy studies present various theoretical frameworks that allow scholars and practitioners to make sense of these developments in a structured and systematic fashion. In this paper, we combined the collective learning framework with documentary data and process tracing analysis to describe, first, the features of the COVID‐19 collective learning setting in Ghana. Next, we explored the linkages among learning processes, learning products, and COVID‐19 mitigation. We found that diverse policy actors operated at distinct levels of government and performed different functions in managing the pandemic. Furthermore, we confirmed all three phases of learning (acquisition, translation, and dissemination) in Ghana's context. Lastly, policies, such as public gathering management, mandatory mask‐wearing, partial lockdown, and fiscal and tax reliefs enabled the government to mitigate the pandemic's impact on people. We conclude by highlighting the implications of these findings for policy learning scholarship. 摘要: 2019冠状病毒病（COVID‐19）已为全球政府和人民带来显著的不确定性和干扰。政策研究展示了不同理论框架，以供学者和从业人员从结构化和系统性方式理解这些发展。本文中，我们将集体学习框架与文献数据及过程追踪分析相结合，描述加纳COVID‐19集体学习情境的特征。随后，我们探究了学习过程、学习结果和COVID‐19缓解之间的联系。我们发现，不同的政策行动者在独特的政府层面进行操作，并在管理大流行一事中发挥不同作用。此外，我们证实了加纳情境下学习的三个阶段（获取、转化和传播）。最后，与例如公共集会管理、强制佩戴口罩、局部封城、以及财政和税收减免相关的一系列政策都为政府缓解大流行对人们造成的影响一事提供适宜条件。我们的结论强调了这些研究发现对政策学习文献产生的意义。 Resumen: COVID‐19 ha creado una gran incertidumbre y trastornos entre los gobiernos y las personas de todo el mundo. Los estudios de políticas presentan varios marcos teóricos que permiten a los académicos y profesionales dar sentido a estos desarrollos de una manera estructurada y sistemática. En este artículo, combinamos el marco de aprendizaje colectivo con datos documentales y análisis de seguimiento de procesos para describir, en primer lugar, las características del entorno de aprendizaje colectivo COVID‐19 en Ghana. A continuación, exploramos los vínculos entre los procesos de aprendizaje, los productos de aprendizaje y la mitigación de COVID‐19. Descubrimos que diversos actores políticos operaban en distintos niveles de gobierno y desempeñaban diferentes funciones en el manejo de la pandemia. Además, confirmamos las tres fases del aprendizaje (adquisición, traducción y difusión) en el contexto de Ghana. Por último, políticas como la gestión de reuniones públicas, el uso obligatorio de máscaras, el cierre parcial y las desgravaciones fiscales permitieron al gobierno mitigar el impacto de la pandemia en las personas. Concluimos destacando las implicaciones de estos hallazgos para la erudición del aprendizaje de políticas.